Leaf Preference of Heliothrips hαemorrhoidαlis (Thysonoptera: Thripidae) on Vιburnum tinus - Koufos, V. Α.; Perdikis, D. CH. (ENTOMOLOGIA HELLENICA, 2002)
The leaf preference of larvae, pupae and adults of Heliothrips haemorrhoidalis (Buche) (Thysanoptera: Thripidae), a serious pest of several ornamental plants, were studied on Viburnum tinus. Leaves were sampled for thrips from the base, middle and distal end of viburnum twigs at weekly intervals from April 11 to September 15, 2000. The population of this thrips was observed at high levels of between 10 to 76 thrips per leaf, till the middle of June when it sharply declined to zero, probably due to high temperatures. Higher populations developed on the basal than on the middle leaves. The lowest populations were recorded on the distal leaves. The predator Orius vicinus (Ribaut) (Hemiptera: Anthocoridae) was recorded in low numbers and therefore its effect on thrips populations was considered negligible.